In silico and In vitro Screening of Medicinal Plants from Brazilian Traditional Medicine for Anti-Helicobacter pylori Activity - Mendes, Campili; Monteiro, Jéssica Raquel Borges; Romagna, Rodrigo de Almeida; Rodrigues de Jesus da Conceição, Aliny; Henrique Tregnago, Pedro; Eiriz Feu, Amanda; Gonçalves, Rita de Cássia Ribeiro; Borges, Warley de Souza; Kuster, Ricardo Machado; Kitagawa, Rodrigo Rezende (Planta Medica, 2025)
Medicinal plants and their phytocompounds are valuable shortcuts for discovering new, safer biologically active compounds or herbal medicines with reduced adverse effects. In this study, medicinal plant species were initially selected from Brazilian traditional medicine using a database of in silico and in vitro studies. A virtual screening study was carried out with a phytochemical database previously reported in the literature. The biological activity was evaluated in silico by PASS Online and molecular docking, then validated by in vitro anti-Helicobacter pylori assay. The chemical profile of the species was obtained by ESI(±)FT-ICR MS and LC-MS-DAD analysis. Vernonia condensata, Bauhinia forficata, Jatropha gossypiifolia, and Sonalum paniculatum were selected based on a survey of the literature for use of gastric diseases and anti-Helicobacter pylori potential. After PASS analysis, Jatropha gossypiifolia was selected for in vitro study because its compounds showed anti-H. pylori activity potential, inhibiting fumarate reductase enzyme. J. gossypiifolia extracted showed MIC of 64 µg/mL and MBC of 128 µg/mL in the in vitro anti-H. pylori assay. ESI(±)FT-ICR MS and LC-MS-DAD analysis showed compounds such as luteolin (1), isovitexin (2), luteolin-7-O-glucoside (3), isoorientin (4), and 3-genistein-8-C-glucoside (5). Molecular docking analysis showed a potential interaction of compounds in the enzyme active site such as hydrogen bonds with Arg404 and a similar interaction to fumaric acid, except for isoorientin (4). J. gossypiifolia showed promising activity and may represent a future alternative to treat H. pylori infections and their deleterious effects, reinforcing the therapeutic potential of this plant.
Keywords: medicinal plants; Helicobacter pylori; virtual screening; fumarate reductase; Jatropha gossypiifolia; Euphorbiaceae